Trabalho e formação continuada de professores de educação especial durante a pandemia da Covid-19: precarização, resistência e luta - Magalhães, Gianni Marcela Boechard (2023)
From the year 2020 onwards, due to the covid-19 pandemic, Brazil initiated political and emergency measures by adopting telework, or home office work, as a possibility of guaranteeing education through remote assistance. This study thesis highlights the fact that the need of social distancing, due to the covid-19 pandemic, makes the educational field - in its actions of continuing teacher’s training and school assistance - effective in consolidating the expansion of the privatization of education system strengthened by the expansion of the educational technology market. Furthermore, virtual platforms appeared as tools for flexibility and concomitant precarious teaching work. In this basis, even under precarious conditions, the offered ongoing education aimed to contribute to planning and teaching practices. However, this kind of aid proved to be insufficient to guarantee the right to education for public school students, especially those who have been historically denied to this right and face prejudice and discrimination in society, such as students target of the special education, as well as, for training, which should aim a humanizing and emancipating horizon for all students. That said, this research aims to investigate the teaching work of special education teachers in the context of the covid-19 pandemic, considering the continuing education of special education teachers in a specific county of Espírito Santo state. We use as a theoric-methodological framework the historical-dialectical materialism, striving for understanding the social determinants, structure and dynamics of the object of study, in order to reproduce its essence. For that, we resorted to bibliographical, documental and case studies.Through the analysis of the data found, we realized that the adoption of telework, as a possibility of maintaining the teaching offer in the context of the covid-19 pandemic, promoted the flexibility of teaching work through technological resources: virtual platforms (Google Classroon, WhatsApp , Meet, Facebook, Youtube), cell phone, television, among others. These resources were adopted even though not all teachers having concrete access conditions and adequate training. The initiatives carried out in the continuing education area for the appropriation of teachers' knowledge to deal with virtual platforms and the necessary knowledge for their pedagogical action, associated with the precarious conditions of their work were not enough to maintain education and meet the demands produced at the time, many of which historical and structural demands. These conditions had significant implications for the educational access of students target of the special education, especially for those with disabilities, such as the emptying of knowledge and the reduction and inconsistency of their school attendance.